A case study : constraint faced by Open and Distance learners - Chiam , Chooi Chea; Raziana Che Aziz (2012)
Malaysia aims to achieve zero illiteracy rates by the year 2020 and hence the concept of open and distance learning (ODL) as well as lifelong learning (LLL) were introduced in the Malaysian education system. Open University Malaysia (OUM) is the first ODL institution in Malaysia. Other than that, OUM was given the head start with the implementation of the flexible entry (FE) in Malaysia after the Ministry of Higher Education has create the way for greater access into the Malaysian higher education and lifelong learning opportunities in year 2006. The concept of ODL was well-received by the public. As at Jan 2012, OUM has approximately 107,000 cumulative learners in the system. Nevertheless, most ODL learners faced much difficulties and constraints in their quest to pursue their tertiary education eg. time management, motivation, basic knowledge etc. This paper discusses the challenges and difficulties faced by the ODL learners in Negeri Sembilan Learning Centre, Open University Malaysia. The data for the paper is collected using paper-andpencil survey and the results are generated using descriptive analysis. The discussions of this paper will be able to give an insight to the administrator in determining the ways to assist these learners and hence would be able to provide a better teaching-learning for ODL learners. It is found that the three main problems faced by ODL learners is the preparation of assignment and test, English language proficiency and time management. (Abstract by authors)